PROSES PEMBUATAN SERBUK LOGAM DENGAN METODA ATOMISASI LAS OKSI-ASITILEN - Muhammad Ridlwan; Alva Edy Tontowi (Teknoin, 2005)
Atomization is the most common method for producing powders from metal. There are three atomization methods in powder fabrication : water atomization, gas atomization, and centrifugal atomization. Atomization was being developed to increase powder quality and process productivity. A new atomization method is possible to find by using another energy resources. Oxy-acetylene can be used as an energy resource in atomization. In this research, powders are made by oxy-acetylene atomization method. Material in wire form is melted in oxy-acetylene flame, which has operating temperature around 3480oC, and atomized to form a fine spray. The fine molten droplets rapidly solidify forming a powders. This research investigate the variation of wire diameter and flame gun attacking angle on atomization process efficiency and production rate. Wire material which used in this research is commercial steel wire with 0.75 mm; 1.25 mm; 1.50 mm in diameter. Flame gun attacking angle is varied 25o, 30o, 35o, 40o, and 45o.Result shows that oxy-acetylene atomization method can be used to produce metal powders. The characteristic of powders which produced by this atomization method have spherical shape, 75 m – 90 m in size, oxidized, and carburized. The efficiency and production rate of the atomization process are around 12.2% and 0.1429 gram/minute. This efficiency and production rate are influenced by wire diameter. Bigger wire diameter results higher efficiency, but lower production rate. For 1.25 mm diameter of commercial wire steel, an optimum efficiency of atomization process, 15.1%, are resulted by 30o of flame gun attacking angle.Keywords : powder fabrication, oxy-acetylene atomization method